INTERSUBJECTIVE CONSTRUCTION OF MSME ACTORS IN UNDERSTANDING ENTREPRENEURIAL MARKETING, ORGANIZATIONAL ENVIRONMENT, AND INTELLECTUAL CAPITAL IN FORMING BUSINESS PERFORMANCE - Muh. Husriadi; Usman. M; La Ode Agus Said (Adisam Publisher, 2026)
This study examines how the intersubjective constructs of MSMEs in Kendari City influence their interpretation of entrepreneurial marketing, the organizational environment, and intellectual capital in shaping business performance. In the context of MSMEs operating with limited resources and a dynamic environment, there is still a gap in understanding regarding the role of shared meaning and social interaction as mediators between strategy and performance. The purpose of this study is to analyze these intersubjective constructs and their implications for business performance. The study used a qualitative approach with a phenomenological design, involving in-depth interviews with MSMEs in Kendari City, and analyzed data using the Miles and Huberman model. The results indicate that entrepreneurial marketing is interpreted as relational personalization and community-based marketing, the organizational environment as a social network managed through deliberation, and intellectual capital as practical knowledge and mutually reinforcing social relationships. Business performance is understood not only from a financial perspective, but also from a perspective of sustainability, customer trust, and community support. Consequently, this study recommends strengthening the capacity of MSME communities, digital-based training, and developing policies that support the local entrepreneurial ecosystem.